A Qualitative Study on the Determinants and Optimization Strategies for Faculty Engagement in University Governance (Journal of Interdisciplinary Insights, 2024)
This qualitative study investigates the determinants and optimization strategies for faculty engagement in university governance at Shandong XX University, China. Using in-depth interviews with 30 participants, including 10 university officials and 20 faculty members, the research identifies key organizational, cultural, and individual factors influencing faculty participation. Findings highlight the importance of clear governance structures, institutional support, manageable workloads, a supportive institutional culture, positive leadership attitudes, and recognition of faculty contributions. The study proposes several optimization strategies, such as enhancing governance transparency, strengthening support systems, managing workloads effectively, fostering a collaborative culture, recognizing and rewarding participation, and improving communication channels. These strategies aim to create an environment that encourages active faculty involvement in governance, ultimately leading to more effective decision-making processes and improved institutional outcomes. The implications for university governance and the broader academic community are discussed, along with the study's limitations and suggestions for future research.